Internet of Things (IoT) in agriculture industries - Adesta, Erry Yulian Triblas; Agusman, Delvis; Avicenna, Avicenna (Institute of Advanced Engineering and Science (IAES) Indonesia Section, 2017)
The IoT applications in the agriculture industry are intertwined in many ways, creating a hybrid construct of traditional businesses with digital connectivity implementations. Strategic issues and principles on the assimilation of IoT solutions are prevail through time: investment costs, data interconnectivity, management and analysis, as well as data security. The agriculture industry is expected to be always alerted for the changes that may apply, with all the contemporary challenges and future directions responding to the situations, so it can reap the optimum use of the IoT connectivity.